Neurocognitive Effects of Ketamine and Esketamine for Treatment-Resistant Major Depressive Disorder: A Systematic Review. Issue 5 (September 2021) - Souza-Marques, Breno; Santos-Lima, Cassio; Araújo-de-Freitas, Lucas; Vieira, Flávia; Jesus-Nunes, Ana Paula; Quarantini, Lucas C.; Sampaio, Aline S.
Abstract: Learning objective: After participating in this activity, learners should be better able to: Analyze the effects of ketamine and esketamine on individuals with treatment-resistant depression Introduction: Cognitive impairment is commonly present in individuals with treatment-resistant depression, especially in attention, memory, and executive functions. These deficits are related to symptom severity, remission rates, and functional impairments during and after the acute phase of the disorder. Ketamine, an N-methyl-D-aspartate antagonist previously used as an anesthetic, brings promising antidepressant results. This study systematically reviews the neurocognitive effects of ketamine and esketamine in patients with treatment-resistant major depressive disorder. Methods: Systematic searches were conducted at Embase, PubMed, and PsycINFO using the terms depression, ketamine, and cognition. Title, abstract, and full-text reading were conducted independently by two of the authors (BSM and CSL). Risk of bias, study design, neuropsychological outcomes, and neuroimaging data were recorded. Results: From a total of 997 hits, 14 articles were included. One study reported cognitive impairment after ketamine treatment for processing speed and verbal memory. Five studies reported improvements in processing speed, verbal memory, visual memory, working memory, or cognitive flexibility. The esketamine study suggested no changes to performance. Lower attention, slower processing speed, and higher working memory are reported as predictors of antidepressant response. Brain areas for emotional and reward processing, including the amygdala, insula, and orbitofrontal cortex, show a normalizing tendency after ketamine. Conclusions: Ketamine and esketamine do not seem to exert significant deleterious neurocognitive effects in the short or long term in individuals with treatment-resistant depression. Results suggest neuropsychological functions and brain areas commonly impaired in treatment-resistant depression may especially benefit from subanesthetic ketamine infusions. Key questions that remain unanswered are discussed. Abstract : Supplemental digital content is available in the text.